Power Bag: Equipamiento para Optimizar las Cargas y Desplazamientos en Actividades Scout de la Comunidad Centauros - González Rocha, Juan Carlos (Universidad Antonio Nariño, 2023)
Power Bag is the result of five years of training in Industrial Design at the university Antonio Nariño, in turn an initiative that seeks to formalize processes, objects and dynamics within the core of an organization dedicated and interested in the management and use of solid waste, as is the World Scout organization more precisely in the branch of Community of Walkers from group 64 Jambonoé of the city of Bogotá.